Label-free non-linear imaging through a multimode fiber endoscope - Tragardh, Johanna; Pikalek, Tomas; Cifuentes, Angel; Meyer, Tobias; Akimov, Denis; Popp, Jurgen; Cizmar, Tomas (Optics InfoBase Conference Papers, 2020)
A GRIN multimode fiber (125 m diameter, 0.29 NA) is transformed into a laser scanning microscope using wave-front shaping on an SLM. We demonstrate label-free non-linear microscopy, namely coherent anti-Stokes Raman scattering (CARS) and SHG.
CRIS-Team Scopus Importer:2023-04-20